SIS, Grigori Tokaev, and the London Controlling Section: New Perspectives on a Cold War Defector and Cold War Deception. (November 2019) - Dylan, Huw
This article examines British deception during the early years of the Cold War, and how a Soviet defector named Grigori Tokaev contributed to British plans and operations. Tokaev provided valuable insights into the Soviet Union, allowing British intelligence to craft more intricate deception operations, political and military. The manner in which he was used, and the extent to which his idiosyncrasies were tolerated, underline the difficulties the British authorities faced as they attempted to apply the lessons of the Second World War deception to the Cold War environment. The case offers new perspectives on both the relatively under-examined subject of British deception operations against the USSR, and the history of one of the most prominent Cold War defectors.